Design and implementation of a mechatronic system for monitoring worker exposure in cold storage facilities - Fajardo-Pruna, Marcelo; Lopez-Estrada, Luis; Barbery, Jhon; Medina, Guillermo (EASI: Ingeniería y Ciencias Aplicadas en la Industria, 2024)
In response to the increasing need for enhanced occupational safety in cold storage facilities, this study presents the design and validation of a mechatronic time control device specifically developed for monitoring the exposure times of warehouse operators in a multinational company. Over the past two decades, Ecuador has significantly increased regulations to safeguard worker health and safety. In compliance with these regulations, this research addresses the challenges operators face when exposed to sub-zero temperatures during their work shifts. The proposed system integrates mechanical, electronic, and control components to systematically track and manage operators’ time within cold rooms, ensuring compliance with predefined safety thresholds. A NodeMCU microcontroller, digital temperature sensors, and a robust communication interface form the device’s core. This device records entry and exit times, monitors ambient conditions, and triggers alerts when exposure limits are approached. Extensive validation was conducted using a 3D-printed resin prototype, demonstrating the device’s capability to function effectively in harsh environments. The system’s efficacy was evaluated through real-world testing, where operators used the prototype during their shifts. Data collected confirmed the device’s reliability in tracking exposure times and enhancing worker safety.